Reproductive potential of fall armyworm Spodoptera frugiperda (J.E. Smith) and effects of feeding on diverse maize genotypes under artificial infestation - Anyanda, Geoffrey N.; Bruce, Anani Yaovi; Makumbi, Dan; Ahonsi, Monday O.; Kahuthia-Gathu, Ruth; Namikoye, Samita E.; Beyene, Yoseph; Boddupalli, P.M. (Frontiers Media, 2022)
Fall armyworm (FAW) Spodoptera frugiperda (J.E. Smith) has become a major threat to maize production in Africa. In this study, six maize genotypes were assessed for their resistance to FAW under artificial infestation in both laboratory and net house conditions. These included two FAW-tolerant hybrids (CKHFAW180294 and CKH191221), two commercial hybrids (WE2115 and CKH10717), and two open-pollinated varieties (ZM523 and KDV4). Larval development time and reproductive potential were assessed on maize leaves in the laboratory and a life table for FAW was constructed. The maize genotypes were also artificially infested with three FAW neonates at two phenological stages (V5 and V7) and reproductive stage (R1) in the net house. Leaf and ear damage scores were recorded on a scale of 1–9. Larval development time varied significantly between maize genotypes with the highest on CKH191221 (16.4 days) and the lowest on KDV4 (13.7 days). The intrinsic rate of natural increase for life tables varied from 0.24 on CKH191221 to 0.41 on KDV4. Mean generation time of FAW ranged from 17.6 to 22.8 days on KDV4 and CKH191221, respectively. Foliar damage was the lowest on CKH191221, and the highest on KDV4 at V7 infestation stage in week 1. CKH191221 had the lowest ear damage score, whereas ZM523 had the highest scores at V5 infestation stage. The highest and lowest yield reductions were observed on ZM523 (64%) at V7 infestation stage and CKHFAW180294 (6%) at R1 infestation stage, respectively. The results indicated the potential for developing tropical mid-altitude maize germplasm with native genetic resistance to FAW.